Liminal movement by digital platform‐based sharing economy ventures: The case of Uber Technologies - Garud, Raghu; Kumaraswamy, Arun; Roberts, Anna; Xu, Le (Strategic Management Journal, 2022)
Abstract Research Summary We explore the challenges that digital platform‐based sharing economy ventures confront in establishing legitimacy for their business models by examining the dynamics that ensued when Uber Technologies deployed its ridesharing business model in four U.S. cities. Uber entered each city to jump‐start network effects by establishing cognitive legitimacy while deepening a sociopolitical legitimacy crisis that emerged due to mismatches between its business model and existing regulations. Operating between existing categories, Uber used a series of interrelated market and nonmarket strategies, which we label as liminal movement, to generate cognitive and sociopolitical legitimacy. Managerial Summary Sharing economy ventures based on digital platforms confront market and institutional challenges in each context they enter. On entry, these ventures must rapidly build an ecosystem of users and service providers, and engage with local regulators, administrators, and social groups in order to gain acceptance. The key to a venture's survival and success is liminal movement or in other words, its ability to adapt its digital platform and business model to continually leverage opportunities and address concerns as they emerge.